Study of Ecological Design of Residential Complexes Using SPSS to Elevate Resident Satisfaction - Kolbadinejad, Soheil Malekpour; Ravasjan, V. Malekpour; Darvish, A. (Makara Journal of Technology, 2019)
This article reports the general residential satisfaction, affecting ecological factors, and their importance in area in Tehran. The collected field data was analyzed using SPSS. Cronbach's alpha variable was used to determine the reliability of the questionnaire and the Friedman test was used to assess priorities that influence residential satisfaction. The results show that the quality of residential environments and general satisfaction of their residents may be enhanced by identifying these criteria and making appropriate plans for their improvement.